Comparative life cycle assessment of sewer corrosion control by iron salts: Suitability analysis and strategy optimization. (1st August 2021) - Wang, Xiuheng; Li, Lanqing; Bai, Shunwen; Yuan, Zhiguo; Miao, Jingyu; Wang, Mengyue; Ren, Nanqi
Highlights: A life cycle assessment of iron salts dosing technology to control sulfide-induced concrete sewer corrosion. From an LCA perspective, iron salts dosing technology is more preferable in severe corrosion conditions. Dosing ferric chloride has a unique advantage in improving most environmental impacts, except toxicity-related impacts. Compared with dosing ferric chloride, dosing ferrous chloride is superior in all impact categories. More life cycle assessment and life cycle cost analysis on integrated water system chemical management are necessary. Abstract: Sewer deterioration caused by sulfide-induced concrete corrosion is spreading worldwide. Within the strategies to overcome this problem, dosing iron salts into the pipeline has attracted more attention. However, there is not yet research that evaluates this method whether it is overall environmentally friendly. Here, we conducted a comparative Life Cycle Assessment (LCA) to adjudge the benefits of dosing ferric chloride over non-dosing option in three different H2 S concentration levels (High, Medium, Low). Compared with taking no precautions, dosing ferric chloride performs better for all impact categories only in High H2 S situation, which can reduce the environmental impacts by 10% to 50%. In Medium H2 S situation, dosing ferric chloride shows lower environmental impacts of Global Warming, Fossil Fuel Depletion, Acidification, and Eutrophication, while leads to the deterioration of Human Toxicity and Freshwater Ecotoxicity by 10% and 13%, respectively. In Low H2 S situation, dosing ferric chloride performs even worse for all impact categories. Therefore, from an LCA perspective, this study recommends iron salts dosing technology to be applied in severe corrosion conditions caused by high H2 S concentrations. Contribution analysis shows that asphalt and diesel consumed during the sewer construction and renovation dominate all impact categories for non-dosing option, whereas the main contributor of Human Toxicity and Freshwater Ecotoxicity is shifted to ferric chloride production in dosing option, average at around 50%. Sensitivity analysis on the length of pipes protected by iron salts confirms that the initial dosing location is more preferable to be set at upstream of the sewer system. From an LCA perspective, as alternatives to ferric chloride, ferrous chloride is superior in all impact categories, and ferric sulfate could reduce the toxicity-related impacts and other effects at the expense of exacerbation of acidification. In the end, a systematic optimization of salts dosing should be considered in urban sewer management practice. Graphical abstract: Image, graphical abstract